Frovatriptan succinate intranasal delivery for brain targeting – in vivo study.‎ - hamzah, Mohammed layth; Kassab, Hanan Jalal (The Iraqi Journal of Veterinary Medicine, 2023)
Muco-adhesive gel formulations are advantageous in extending the stay at the nasal ‎absorption place, promoting drug absorption. Frovatriptan succinate (FVT) exhibits a 35% ‎oral bioavailability and undergoes hepatic metabolism, making it a viable candidate for ‎nasal delivery. This study aimed to assess novel FVT intranasal formulation for brain ‎targeting in rat animal models. A total of 78 female rats (Rattus norvegicus domestica, ‎Wister albino rats) were randomly divided into three groups: group A (considered a ‎negative control), group B (includes 36 rats given FVT IV solution), and group C (includes ‎‎36 rats given FVT binary ethosome in situ gel intranasally). Drug levels in plasma and brain ‎tissue were measured using HPLC methods. In all periods, for both brain tissue ‎concentrations of FVT and the brain-to-plasma ratio of FVT, it was significantly higher in ‎Group C compared to Group B. Nasal administration of FVT showed higher brain Tmax, ‎Cmac, and AUC compared to IV administration, with 239.83% higher accumulation of FVT ‎when nasal formulation used compared to IV administration. In conclusion, in situ gel has ‎demonstrated its efficacy in facilitating the delivery of frovatriptan succinate via the nasal ‎route. The convenience of the administration process, combined with reduced frequency of ‎administration, contributes to improved patient adherence‎‎‎.